If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x(x + -8) = (6x + 4) + -8 Reorder the terms: -2x(-8 + x) = (6x + 4) + -8 (-8 * -2x + x * -2x) = (6x + 4) + -8 (16x + -2x2) = (6x + 4) + -8 Reorder the terms: 16x + -2x2 = (4 + 6x) + -8 Remove parenthesis around (4 + 6x) 16x + -2x2 = 4 + 6x + -8 Reorder the terms: 16x + -2x2 = 4 + -8 + 6x Combine like terms: 4 + -8 = -4 16x + -2x2 = -4 + 6x Solving 16x + -2x2 = -4 + 6x Solving for variable 'x'. Reorder the terms: 4 + 16x + -6x + -2x2 = -4 + 6x + 4 + -6x Combine like terms: 16x + -6x = 10x 4 + 10x + -2x2 = -4 + 6x + 4 + -6x Reorder the terms: 4 + 10x + -2x2 = -4 + 4 + 6x + -6x Combine like terms: -4 + 4 = 0 4 + 10x + -2x2 = 0 + 6x + -6x 4 + 10x + -2x2 = 6x + -6x Combine like terms: 6x + -6x = 0 4 + 10x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(2 + 5x + -1x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(2 + 5x + -1x2)' equal to zero and attempt to solve: Simplifying 2 + 5x + -1x2 = 0 Solving 2 + 5x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -2 + -5x + x2 = 0 Move the constant term to the right: Add '2' to each side of the equation. -2 + -5x + 2 + x2 = 0 + 2 Reorder the terms: -2 + 2 + -5x + x2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5x + x2 = 0 + 2 -5x + x2 = 0 + 2 Combine like terms: 0 + 2 = 2 -5x + x2 = 2 The x term is -5x. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5x + 6.25 + x2 = 2 + 6.25 Reorder the terms: 6.25 + -5x + x2 = 2 + 6.25 Combine like terms: 2 + 6.25 = 8.25 6.25 + -5x + x2 = 8.25 Factor a perfect square on the left side: (x + -2.5)(x + -2.5) = 8.25 Calculate the square root of the right side: 2.872281323 Break this problem into two subproblems by setting (x + -2.5) equal to 2.872281323 and -2.872281323.Subproblem 1
x + -2.5 = 2.872281323 Simplifying x + -2.5 = 2.872281323 Reorder the terms: -2.5 + x = 2.872281323 Solving -2.5 + x = 2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 2.872281323 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 2.872281323 + 2.5 x = 2.872281323 + 2.5 Combine like terms: 2.872281323 + 2.5 = 5.372281323 x = 5.372281323 Simplifying x = 5.372281323Subproblem 2
x + -2.5 = -2.872281323 Simplifying x + -2.5 = -2.872281323 Reorder the terms: -2.5 + x = -2.872281323 Solving -2.5 + x = -2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -2.872281323 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -2.872281323 + 2.5 x = -2.872281323 + 2.5 Combine like terms: -2.872281323 + 2.5 = -0.372281323 x = -0.372281323 Simplifying x = -0.372281323Solution
The solution to the problem is based on the solutions from the subproblems. x = {5.372281323, -0.372281323}Solution
x = {5.372281323, -0.372281323}
| -6r-10s+8r+4s-6= | | x^2+2x=89 | | 3x^4+9x^3-25x^2+15x-50=0 | | 2(5+-.5y)+y=10 | | 9y-2+9y=6 | | 18=-6-x | | Y=6x^7-2cosx | | =12v^4-8v^3 | | 7t-4.6=10.1 | | 3(xy+w*w)+2xy-2w*2w= | | 9w-18+5w+2=180 | | 9.5+p-6.8=7.3 | | -5s+9=-6 | | (5y+5)-5y=5 | | 15g-3(4g-6)=3g+9-9g | | 6+2x=4x-2 | | 2x+1=10x-3(x-1) | | 3y^2-15y=12 | | x^2+x-80=0 | | 6y+7=5y-5 | | 4a+2b-3-6a-5b= | | 5.5y=71.5 | | 7-6a=7a | | -3(4y-2)-y=-3(y-5) | | -2x^2+6x+8=0 | | 3x+2(x+3)=31 | | 14x-(4+5x)= | | (-11)-18= | | 2x+5(x-4)=36 | | 4(xy)=(4y) | | 6+10(15)= | | 4x+11=-12x-37 |